High Pressure Processing Impact on Emerging Mycotoxins (ENNA, ENNA1, ENNB, ENNB1) Mitigation in Different Juice and Juice-Milk Matrices - Noelia Pallarés; Albert Sebastià; Vicente Martínez-Lucas; Rui Queirós; Francisco J. Barba; Houda Berrada; Emilia Ferrer (Foods, 2022)
The aim of the present study was to investigate the potential of high-pressure processing (HPP) (600 MPa during 5 min) on emerging mycotoxins, enniatin A (ENNA), enniatin A1 (ENNA1), enniatin B (ENNB), enniatin B1 (ENNB1) reduction in different juice/milk models, and to compare it with the effect of a traditional thermal treatment (HT) (90 °C during 21 s). For this purpose, different juice models (orange juice, orange juice/milk beverage, strawberry juice, strawberry juice/milk beverage, grape juice and grape juice/milk beverage) were prepared and spiked individually with ENNA, ENNA1, ENNB and ENNB1 at a concentration of 100 µg/L. After HPP and HT treatments, ENNs were extracted from treated samples and controls employing dispersive liquid-liquid microextraction methodology (DLLME) and determined by liquid chromatography coupled to ion-trap tandem mass spectrometry (HPLC-MS/MS-IT). The results obtained revealed higher reduction percentages (11% to 75.4%) when the samples were treated under HPP technology. Thermal treatment allowed reduction percentages varying from 2.6% to 24.3%, at best, being ENNA1 the only enniatin that was reduced in all juice models. In general, no significant differences (p > 0.05) were observed when the reductions obtained for each enniatin were evaluated according to the kind of juice model, so no matrix effects were observed for most cases. HPP technology can constitute an effective tool in mycotoxins removal from juices.